Maintenance haemodialysis with low dialysate flow rates in Senegal - Mbengue, Mansour; Diagne, Seynabou; Macondo, Edgard Adam; Luong, Nhan; Massy, Ziad A; Niang, Abdou (African Journal of Nephrology, 2022)
Introduction: The objective of the study reported here was to demonstrate that maintenance haemodialysis using a reduced dialysate flow rate of 300 mL/min (RQD) is not inferior to haemodialysis using the standard flow rate of 500 mL/min (SQD) in respect of the delivered dose of dialysis. Methods: A prospective, single-centre, sequential study was performed at the haemodialysis centre of Pikine Hospital in Dakar. Twenty patients were included. During the first week, three haemodialysis sessions were performed with SQD and during the second week three haemodialysis sessions were conducted with RQD for each patient. Results: For SQD, the mean eKt/V was 1.38 ± 0.58. There were 38 (63%) sessions with eKt/V greater than 1.2 and 16 patients (80%) had adequate dialysis, based on the average eKt/V. For RQD, the mean eKt/V was 1.2 ± 0.43 with 25 sessions (42%) having an eKt/V greater than 1.2. There were 11 patients (55%) with adequate dialysis. The dialysis dose was higher with the SQD prescription (P < 0.001). Ten patients with dry weight ≤60 kg had adequate dialysis with RQD. Cases of hypokalaemia were significantly higher with the SQD (P = 0.001). Conclusions: RQD appears to be inferior in terms of dialysis dose. However, for patients with dry weight ≤60 kg, adequate dialysis could be delivered with RQD, consequently allowing substantial saving of water in haemodialysis.